Streptococcus Mutans biofilm influences on the antimicrobial properties of glass ionomer cements - Fúcio, Suzana B. P.; de Paula, Andréia B.; Sardi, Janaina C. O.; Duque, Cristiane [UNESP]; Correr-Sobrinho, Lourenço; Puppin-Rontani, Regina Maria (FapUNIFESP (SciELO), 2016)
The aim of this study was to evaluate the in vitro antibacterial and biofilm inhibition properties of glass ionomer restorative cements. Ketac Nano, Vitremer, Ketac Molar Easymix and Fuji IX were analyzed using the following tests: a) agar plate diffusion test to evaluate the inhibitory activity of cements against S. mutans (n=8); b) S. mutans adherence test by counting colony-forming units after 2 h of material/bacteria exposure (n=10); c) biofilm wet weight after seven days of bacterial accumulation on material disks, with growth medium renewed every 48 h (n=10); d) pH and fluoride measurements from the medium aspired at 48 h intervals during the 7-day biofilm development (n=10). Data from the a, b and c tests were submitted to Kruskal-Wallis and Mann-Whitney tests and the fluoride-release and pH data were submitted to two-way ANOVA and Tukey tests (α=5%). Vitremer followed by Ketac Nano showed the greatest inhibitory zone against S. mutans than the conventional ionomers. Vitremer also showed higher pH values than Ketac Nano and Fuji IX in the first 48 h and released higher fluoride amount than Ketac Nano e Ketac Molar Easymix throughout the experimental period. The chemical composition of restorative glass ionomer materials influenced the antibacterial properties. The resin modified glass ionomer (Vitremer) was more effective for inhibition of S. mutans and allowed greater neutralization of the pH in the first 48 h. However, the type of glass ionomer (resin modified or conventional) did not influence the weight and adherence of the biofilm and fluoride release.
Keywords: Bacterial adherence; Dental biofilm; Fluoride release; Glass ionomer cements; Nanotechnology; pH; Streptococcus mutans